Polarizing plate and image display device

CN117751309BActive Publication Date: 2026-10-27SUMITOMO CHEM CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202280050005.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-19
Filing Date
2022-06-30
Publication Date
2026-10-27
Estimated Expiration
2042-06-30

AI Technical Summary

Technical Problem

[0007]但是根据报告,在采用此种构成的情况下,在高温环境下偏振板的透射率显著地降低

Benefits of technology

[0034]根据本发明,能够提供一种偏振板,在用于以使固体层接触偏振板的两面的方式构成的层间填充构成的图像显示装置中的情况下,即使暴露于高温环境下,也可以抑制透射率的降低。此外,通过使用本发明的偏振板,能够提供即使暴露于高温环境下也可以抑制透射率的降低的图像显示装置。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004664576170000081
    Figure BDA0004664576170000081
  • Figure BDA0004664576170000082
    Figure BDA0004664576170000082
  • Figure BDA0004664576170000091
    Figure BDA0004664576170000091
Patent Text Reader

Abstract

Provided is a polarizing plate capable of inhibiting a decrease in transmittance in a high-temperature environment. The polarizing plate has a polarizing element in which a dichroic dye is adsorbed and oriented in a polyvinyl alcohol-based resin layer, and a transparent protective film laminated to at least one face of the polarizing element. The polarizing element and the transparent protective film are joined with an adhesive layer formed from an adhesive containing a first compound and a second compound. The first compound is a compound having a nitroxyl radical or a nitroxide radical. The second compound is a cyclodextrin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polarizing plates and image display devices. Background Technology

[0002] Liquid crystal displays (LCDs) are not only used in LCD televisions, but also widely used in personal computers, mobile devices such as mobile phones, and automotive applications such as navigation systems. Typically, an LCD has a liquid crystal panel formed by bonding polarizing plates to both sides of liquid crystal cells with adhesive. The display is achieved by controlling the light from the backlight using the liquid crystal panel. In recent years, organic EL displays have also been widely used, similarly to LCDs, in televisions, mobile devices such as mobile phones, and automotive applications such as navigation systems. In organic EL displays, to suppress the mirror-like effect caused by external light being reflected by the metal electrode (cathode), a circular polarizing plate (a laminate containing polarizing elements and a λ / 4 plate) is sometimes placed on the viewing side surface of the image display panel.

[0003] As mentioned above, polarizing plates are increasingly being used in automobiles as components of image display devices such as liquid crystal displays and organic EL displays. Compared to those used in mobile devices such as televisions and mobile phones, polarizing plates used in automotive image display devices are frequently exposed to high-temperature environments, thus requiring less change in properties at high temperatures (high-temperature durability).

[0004] On the other hand, to prevent damage to the image display panel from impacts from external surfaces, there is an increasing trend of constructing a transparent front panel (sometimes called a "window layer") such as a transparent resin plate or glass plate on the viewing side of the image display panel. In image display devices equipped with touch panels, a configuration is widely adopted where a touch panel is positioned on the viewing side of the image display panel, and a transparent front panel is provided on the viewing side of the touch panel.

[0005] In this configuration, if an air layer exists between the image display panel and transparent components such as the front transparent panel and touch panel, reflected glare from external light will occur due to light reflection at the air layer interface, tending to reduce the visibility of the image. Therefore, there is a growing trend to fill the space between the polarizer disposed on the viewing side surface of the image display panel and the transparent component with a layer other than the air layer, usually a solid layer (hereinafter sometimes referred to as "interlayer filler"). The interlayer filler is preferably a material with a refractive index close to that of the polarizer or the transparent component. As the interlayer filler, adhesives and UV-curable adhesives (see, for example, Patent Document 1) are used to suppress the reduction in visibility caused by reflection at the interface and to bond and fix the components together.

[0006] As described above, the use of structures filled with interlayer fillers is expanding in mobile devices such as cell phones, which are frequently used outdoors. Furthermore, due to increasing demands for visibility in recent years, structures employing a front transparent panel on the surface of the image display panel and filling the space between the panel and the front transparent panel with a solid layer such as an adhesive layer are being researched for automotive applications such as navigation devices.

[0007] However, according to the report, with this configuration, the transmittance of the polarizing plate decreases significantly under high-temperature conditions. Patent Document 2 proposes a solution to this problem by setting the water content per unit area of ​​the polarizing plate to a predetermined amount or less, and by setting the saturated water absorption of the transparent protective film adjacent to the polarizing element to a predetermined amount or less, thereby suppressing the decrease in transmittance.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 11-174417

[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-102353 Summary of the Invention

[0012] The problem that the invention aims to solve

[0013] However, even this type of polarizing plate cannot adequately suppress the decrease in transmittance under high-temperature conditions.

[0014] The object of the present invention is to provide a polarizing plate that can suppress the decrease in transmittance even when exposed to high temperature environments, and an image display device using the polarizing plate.

[0015] Methods for solving problems

[0016] The present invention provides the following polarizing plate and image display device.

[0017] [1] A polarizing plate having a polarizing element obtained by adsorbing and oriented a dichroic pigment on a polyvinyl alcohol-based resin layer, and a transparent protective film laminated on at least one side of the polarizing element.

[0018] The aforementioned polarizing element and the aforementioned transparent protective film are bonded together using an adhesive layer formed from an adhesive containing the first compound and the second compound.

[0019] The first compound mentioned above is a compound containing nitryl radicals or nitroxy radicals.

[0020] The second compound mentioned above is a cyclodextrin.

[0021] [2] According to the polarizing plate described in [1], the first compound mentioned above is an N-oxygen free radical compound.

[0022] [3] According to the polarizing plate described in [1] or [2], wherein the second compound is selected from at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.

[0023] [4] The polarizing plate described in any one of [1] to [3], wherein the adhesive comprises a polyvinyl alcohol resin.

[0024] [5] According to the polarizing plate described in [4], in the adhesive, the content of the first compound is 0.1 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of the polyvinyl alcohol resin.

[0025] [6] According to the polarizing plate described in [4] or [5], wherein in the adhesive, the content of the second compound is more than 1 part by mass and less than 50 parts by mass relative to 100 parts by mass of the polyvinyl alcohol resin.

[0026] [7] The polarizing plate described in any one of [1] to [6], wherein the thickness of the adhesive layer is 0.01 μm or more and 7 μm or less.

[0027] [8] The polarizing plate described in any one of [1] to [7], wherein the polarizing plate is used in an image display device,

[0028] In the above-mentioned image display device, a solid layer is provided in contact with both sides of the polarizing plate.

[0029] [9] An image display device having an image display unit, a first adhesive layer laminated on the observation side surface of the image display unit, and a polarizing plate described in any one of [1] to [8] laminated on the observation side surface of the first adhesive layer.

[0030]

[10] The image display device described in [9] further comprises a second adhesive layer laminated on the observation side surface of the polarizing plate and a transparent component laminated on the observation side surface of the second adhesive layer.

[0031]

[11] According to the image display device described in

[10] , the transparent component is a glass plate or a transparent resin plate.

[0032]

[12] According to the image display device described in

[10] , the transparent component is a touch panel.

[0033] Invention Effects

[0034] According to the present invention, a polarizing plate can be provided that, in an image display device constructed with interlayer filling in a manner in which a solid layer is in contact with both sides of the polarizing plate, suppresses the decrease in transmittance even when exposed to a high-temperature environment. Furthermore, by using the polarizing plate of the present invention, an image display device can be provided that suppresses the decrease in transmittance even when exposed to a high-temperature environment. Detailed Implementation

[0035] The embodiments of the present invention will be described below; however, the present invention is not limited to the following embodiments.

[0036] [Polarizing plate]

[0037] The polarizing plate of this embodiment has a polarizing element obtained by adsorbing and oriented a dichroic pigment onto a polyvinyl alcohol-based resin layer, and a transparent protective film laminated on at least one side of the polarizing element. The polarizing element and the transparent protective film are bonded together using an adhesive layer formed by an adhesive containing a first compound and a second compound. The first compound is a compound having nitroglycerin free radicals or nitroxide free radicals. The second compound is a cyclodextrin.

[0038] Conventional polarizing plates known for their excellent high-temperature durability include those that, even when placed at 95°C for 1000 hours as a standalone polarizing plate, can suppress the decrease in transmittance. However, even with such polarizing plates, in image display devices where one side of the polarizing plate is bonded to the image display unit and the other side is bonded to transparent components such as the touch panel and front panel, forming a configuration where the solid layer and both sides of the polarizing plate are in contact (hereinafter sometimes referred to as an "interlayer filling configuration"), a significant decrease in transmittance can be observed in the central portion of the polarizing plate after being placed at 95°C for 200 hours. This significant decrease in the transmittance of polarizing plates at high temperatures is considered a problem that is particularly prone to occur when image display devices employing an interlayer filling configuration are exposed to high-temperature environments.

[0039] For polarizing plates with significantly reduced transmittance in image display devices composed of interlayer fillers, this is due to the fact that in Raman spectrometry at 1100 cm⁻¹... -1 Nearby (from =CC= key) and 1500cm -1 The presence of peaks near the -C=C- bond suggests the formation of a polyene structure (-C=C). n - It is speculated that the polyene structure is produced by polyene-based resins constituting polarizing elements after dehydration (Patent Document 2,

[0012] paragraph).

[0040] The polarizing plate of this embodiment, when assembled into an image display device with interlayer filling, exhibits excellent high-temperature durability, suppressing the decrease in transmittance even when exposed to high-temperature environments, such as 105°C. This effect is achieved because the polarizing plate has an adhesive layer containing a first compound and a second compound, presumably due to the synergistic effect of the first and second compounds suppressing the polyolefination of the polyvinyl alcohol-based resin constituting the polarizing element. This effect is not limited to cases where the polarizing plate has a low moisture content; it has been confirmed that it also works when the polarizing plate has a high moisture content.

[0041] The polarizing plate of this embodiment may have at least one of the features described in (a) and (b) below.

[0042] (a) The moisture content of the polarizing element is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C.

[0043] (b) The moisture content of the polarizing plate is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C.

[0044] Even when the polarizing plate of this embodiment has features that further define the features of (a) or (b) above as described below (a1) or (b1), it can still improve high-temperature durability.

[0045] (a1) The moisture content of the polarization element is greater than the equilibrium moisture content at 20°C and relative humidity of 45% or 50%, and is less than the equilibrium moisture content at 20°C and relative humidity of 80% or 70%.

[0046] (b1) The moisture content of the polarizing plate is greater than the equilibrium moisture content at 20°C and relative humidity of 45% or 50%, and is less than the equilibrium moisture content at 20°C and relative humidity of 80% or 70%.

[0047] The method for manufacturing a polarizing plate according to this embodiment may include a step of adjusting the moisture content in a manner having at least one of the features described in (a) and (b) above, or it may not include a step of adjusting the moisture content.

[0048] <Polarization element>

[0049] As a polarizing element obtained by adsorbing and orienting dichroic dyes onto a polyvinyl alcohol (hereinafter sometimes referred to as "PVA")-based resin layer, a known polarizing element can be used. Examples of polarizing elements include a stretched film obtained by dyeing a PVA-based resin film (which will become a PVA-based resin layer) with a dichroic dye and then uniaxially stretching it; and an element formed by coating a substrate film with a coating layer (which will become a PVA-based resin layer) onto the substrate film with a coating liquid containing a PVA-based resin, dyeing the coating layer with a dichroic dye, and then uniaxially stretching the laminated film. Stretching can be performed after dyeing with the dichroic dye, or during dyeing, or after stretching.

[0050] The PVA-based resin contained in the PVA-based resin layer can be obtained by saponifying a polyvinyl acetate-based resin. In addition to polyvinyl acetate as a homopolymer of vinyl acetate, copolymers of vinyl acetate with other monomers that can be copolymerized can also be mentioned. Examples of other monomers that can be copolymerized include unsaturated carboxylic acids, olefins such as ethylene, vinyl ethers, and unsaturated sulfonic acids.

[0051] The degree of saponification of the PVA-based resin is preferably 85 mol% or more, more preferably 90 mol% or more, and even more preferably 99 mol% or more and 100 mol% or less. The degree of polymerization of the PVA-based resin is, for example, 1000 or more and 10000 or less, preferably 1500 or more and 5000 or less. The PVA-based resin can be modified, for example, it can be aldehyde-modified polyvinyl formal, polyvinyl acetal, polyvinyl butyral, etc.

[0052] Examples of dichroic pigments that are adsorbed and oriented in a PVA-based resin layer include iodine or dichroic dyes. Iodine is preferred as a dichroic pigment. Examples of dichroic dyes include Red BR, Red LR, Red R, Pink LB, Ruby BL, Bordeaux GS, SkyBlue LG, Lemon Yellow, Blue BR, Blue 2R, Navy RY, GreenLG, Violet LB, Violet B, Black H, Black B, Black GSP, Yellow 3G, Yellow R, Orange LR, Orange 3R, Scarlet GL, Scarlet KGL, Congo Red, Brilliant Violet BK, Supra Blue G, Supra Blue GL, Supra Orange GL, and Direct Sky. The sun protection technologies include Blue, Direct Fast Orange S, and Fast Black.

[0053] The thickness of the polarizing element is preferably 3 μm or more and 35 μm or less, more preferably 4 μm or more and 30 μm or less, and even more preferably 5 μm or more and 25 μm or less. By making the thickness of the polarizing element 35 μm or less, it is easy to suppress the effect of polyolefination of PVA-based resin on the reduction of optical properties under high temperature conditions. By making the thickness of the polarizing element 3 μm or more, it is easy to obtain a polarizing plate that achieves the desired optical properties.

[0054] The polarizing element of the polarizing plate in this embodiment preferably includes a first compound and a second compound. Since the polarizing element and the transparent protective film are bonded together using an adhesive layer formed from an adhesive containing the first and second compounds, it is presumed that a portion of the first compound and a portion of the second compound transferred from the adhesive layer are contained within the polarizing element. By providing an adhesive layer containing the first and second compounds to the polarizing plate having this type of polarizing element, the transmittance is less likely to decrease even when exposed to high temperatures. Furthermore, by providing an adhesive layer containing the first and second compounds, the decrease in polarization degree can be suppressed even when the polarizing plate is exposed to high temperatures. If the polarization degree of the polarizing plate decreases, light leakage (hereinafter sometimes referred to as "orthogonal light leakage") is likely to occur when two polarizing plates are arranged in a manner forming orthogonal Nicol prisms. However, since the polarizing degree of the polarizing plate in this embodiment is less likely to decrease even when exposed to high temperatures, orthogonal light leakage is easily suppressed. It can be inferred that by utilizing the synergistic effect of the first and second compounds contained in the polarization element to suppress the polyolefination of PVA-based resin, the decrease in the transmittance of the polarization plate exposed to high temperature environment can be suppressed, and the decrease in polarization degree can also be suppressed.

[0055] As a method for containing the first compound and the second compound in a polarizing element, examples include a method for transferring the first compound and the second compound from the adhesive layer to the polarizing element as described above; a method for manufacturing a polarizing element containing the first compound and the second compound; and a combination of these two methods. For example, during the manufacturing of the polarizing element, one of the first compound and the second compound may be contained in the polarizing element, and both the first compound and the second compound may be contained in the adhesive layer constituting the polarizing plate.

[0056] As a method for manufacturing a polarizing element containing the first compound and the second compound during the manufacture of the polarizing element, examples include impregnating a PVA-based resin layer in a processing solvent containing the first compound and / or the second compound, or spraying, flowing, or dripping the processing solvent onto the PVA-based resin layer. Among these, the method of impregnating the PVA-based resin layer in a processing solvent containing both the first compound and the second compound is preferred. Specific examples of the first compound and the second compound include compounds exemplified as compounds contained in the adhesive described later.

[0057] The process of impregnating the PVA-based resin layer in a processing solvent containing the first and second compounds can be performed simultaneously with the swelling, stretching, dyeing, crosslinking, and washing processes in the polarization element manufacturing method described later, or it can be performed separately from these processes. The process of including the first and second compounds in the PVA-based resin layer is preferably performed after dyeing the PVA-based resin layer with iodine, and more preferably simultaneously with the crosslinking process after dyeing. According to this method, the color tone variation is small, which reduces the impact on the optical properties of the polarization element.

[0058] (Compound 1)

[0059] The first compound is a compound having a nitryl radical or a nitroxide radical. From the viewpoint of having a free radical that is relatively stable at room temperature and in air, an N-oxygen radical compound (a compound having the functional group CN(-C)-O· (O· represents an oxygen radical, bonded to N)) can be cited as the first compound, and known compounds can be used. Examples of N-oxygen radical compounds include compounds with organic groups having the following structures. Compounds having nitryl radicals or nitroxide radicals can be used alone or in combination of two or more.

[0060] [Chemistry 1]

[0061]

[0062] In the above formula (1), R 1 R represents oxygen free radicals. 2 ~R 5 Independently represents an alkyl group having 1 to 10 hydrogen atoms, where n represents 0 or 1.

[0063] The left side of the dashed part in the above formula (1) represents any organic group or hydrogen atom.

[0064] Examples of compounds having the above-mentioned organic groups include compounds represented by formulas (2) to (5).

[0065] [Chemistry 2]

[0066]

[0067] In the above formula (2), R 1 ~R 5 And n represents the same meaning as above, R 6 This represents a hydrogen atom, or an alkyl, acyl, or aryl group with 1 to 10 carbon atoms; n represents 0 or 1.

[0068] [Chemistry 3]

[0069]

[0070] In the above formula (3), R 1 ~R 5 And n represents the same meaning as above, R 7 and R 8 Independently representing a hydrogen atom, or an alkyl, acyl, or aryl group having 1 to 10 carbon atoms.

[0071] [Chemistry 4]

[0072]

[0073] In the above formula (4), R 1 ~R 5 And n represents the same meaning as above, R 9 ~R 11 Independently representing a hydrogen atom, or an alkyl, acyl, amino, alkoxy, hydroxyl, or aryl group having 1 to 10 carbon atoms.

[0074] [Chemistry 5]

[0075]

[0076] In the above formula (5), R 1 ~R 5 And n represents the same meaning as above, R 12 This refers to a hydrogen atom, or an alkyl, acyl, amino, alkoxy, hydroxyl, or aryl group having 1 to 10 carbon atoms.

[0077] From the perspective of accessibility, in equations (1) to (5) above, R 2 ~R 5 Preferably, it is an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms. In formula (2) above, from the viewpoint of availability, R... 6 Preferably, it is an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. In formula (3) above, from the viewpoint of availability, R... 7 and R 8 Preferably, it is an alkyl group having 1 to 10 carbon atoms, and more preferably, it is a hydrogen atom. In formula (4) above, from the viewpoint of availability, R... 9 ~R 11 Preferably, it is an alkyl group having 1 to 10 hydrogen atoms or carbon atoms independently. In formula (5) above, from the viewpoint of availability, R 12 Preferably, it is hydroxyl, amino, or alkoxy. In the above formulas (1) to (5), from the viewpoint of availability, n is preferably 1.

[0078] Examples of N-oxygen radical compounds include those described in Japanese Patent Application Publication No. 2003-64022, Japanese Patent Application Publication No. 11-222462, Japanese Patent Application Publication No. 2002-284737, and International Patent Publication No. 2016 / 047655. Among these, the 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxygen radical is preferred.

[0079] Examples of compounds that can be cited as the first compound include the following compounds.

[0080] [Chemistry 6]

[0081]

[0082] [In formula (6), R represents a hydrogen atom, or an alkyl, acyl, or aryl group having 1 to 10 carbon atoms.]

[0083] [Chemistry 7]

[0084]

[0085] [Chemistry 8]

[0086]

[0087] From the viewpoint of efficiently capturing free radicals generated in the polyene reaction, the molecular weight of the first compound is preferably 1000 or less, more preferably 500 or less, and even more preferably 300 or less. The lower limit of the molecular weight is not particularly limited; for example, it can be 80.

[0088] (Compound 2)

[0089] The second compound is a cyclodextrin. Cyclodextrins are non-reducing cyclic oligosaccharides composed of glucose linked in a cyclic structure by α-1,4 bonds. The more glucose molecules that constitute a cyclodextrin, the larger the inner diameter of the voids within the molecule. Preferably, the cyclodextrin used as the second compound contains six or more glucose molecules; examples include α, β, γ, and δ-cyclodextrins containing 6, 7, 8, or 9 glucose molecules. Among the α, β, γ, and δ-cyclodextrins, branched cyclodextrins with branched sugar chains containing oligosaccharides such as glucose and maltose are included. Cyclodextrin derivatives, such as those further bonded with alkyl groups such as methyl groups, 2-hydroxyethyl groups, 2-hydroxypropyl groups, 2,3-dihydroxypropyl groups, and 2-hydroxybutyl groups, are also included. One type of cyclodextrin can be used alone, or two or more can be used in combination.

[0090] (Feature(a))

[0091] When the polarizing plate has the aforementioned feature (a), the moisture content of the polarizing element is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C. The moisture content of the polarizing element may also be greater than the equilibrium moisture content of 45% or 50% relative humidity at 20°C and below the equilibrium moisture content of 80% or 70% relative humidity at 20°C. If the moisture content of the polarizing element is less than the equilibrium moisture content of 30% relative humidity at 20°C, the operability of the polarizing element decreases, and it is prone to breakage. If the moisture content of the polarizing element is higher than the equilibrium moisture content of 45% or 50% relative humidity at 20°C, it is presumed that polyolefin formation of the PVA-based resin is easily promoted. However, since the polarizing plate of this embodiment has an adhesive layer containing the first compound and the second compound, it is able to suppress the polyolefin formation of the PVA-based resin.

[0092] As a method to confirm that the moisture content of the polarizing element is within the range of equilibrium moisture content above 30% relative humidity at 20°C and below 80% relative humidity at 20°C, examples include storing the element in an environment adjusted to the aforementioned temperature and relative humidity range, and considering it to have reached equilibrium with the environment if there is no change in mass over a certain period of time; or pre-calculating the equilibrium moisture content of the polarizing element in an environment adjusted to the aforementioned temperature and relative humidity range, and confirming it by comparing the moisture content of the polarizing element with the pre-calculated equilibrium moisture content.

[0093] There are no particular limitations on the method for manufacturing a polarizing element with an equilibrium moisture content of 30% or higher at a temperature of 20°C and a relative humidity of 80% or lower at a temperature of 20°C. For example, a method can be given by storing the polarizing element in an environment adjusted to the above temperature and relative humidity range for 10 minutes or more and 3 hours or less; or a method of heat treatment at a temperature of 30°C or higher and 90°C or lower.

[0094] As another preferred method for manufacturing polarizing elements with the aforementioned moisture content, examples include storing a laminate with a transparent protective film layered on at least one side of the polarizing element, or a polarizing plate made using the polarizing element, in an environment adjusted to the aforementioned temperature and relative humidity range for 10 minutes to 120 hours; or performing a heat treatment at 30°C to 90°C. Alternatively, in the manufacture of an image display device using interlayer filling, a transparent component such as a front panel can be bonded after storing an image display panel with a polarizing plate layered on the image display unit in an environment adjusted to the aforementioned temperature and relative humidity range for 10 minutes to 3 hours, or after heating at a temperature of 30°C to 90°C.

[0095] (Feature (b))

[0096] When the polarizing plate has the aforementioned characteristic (b), the moisture content of the polarizing plate is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C. The moisture content of the polarizing plate may also be greater than the equilibrium moisture content of 45% or 50% relative humidity at 20°C and below the equilibrium moisture content of 80% or 70% relative humidity at 20°C. If the moisture content of the polarizing plate is less than the equilibrium moisture content of 30% relative humidity at 20°C, the operability of the polarizing plate decreases, and it is prone to breakage. If the moisture content of the polarizing plate is high enough to exceed the equilibrium moisture content of 45% or 50% relative humidity at 20°C, it is presumed that the polyolefination of the PVA-based resin is easily promoted. However, since the polarizing plate of this embodiment has an adhesive layer containing the first compound and the second compound, the polyolefination of the PVA-based resin can be suppressed.

[0097] As a method to confirm that the moisture content of the polarizing plate is within the range of equilibrium moisture content above 30% relative humidity at 20°C and below 80% relative humidity at 20°C, examples include storing the plate in an environment adjusted to the above temperature and relative humidity range, and considering it to have reached equilibrium with the environment if there is no change in mass over a certain period of time; or pre-calculating the equilibrium moisture content of the polarizing plate in an environment adjusted to the above temperature and relative humidity range, and confirming it by comparing the moisture content of the polarizing plate with the pre-calculated equilibrium moisture content.

[0098] There are no particular limitations on the method for manufacturing a polarizing plate with an equilibrium moisture content of 30% or higher at 20°C and 80% or lower at 20°C. However, examples include storing the polarizing plate in an environment adjusted to the aforementioned temperature and relative humidity range for 10 minutes to 3 hours; or performing a heat treatment at a temperature of 30°C or higher and 90°C or lower. Alternatively, in the manufacture of an image display device using interlayer filling, the image display panel on which the polarizing plate is laminated can be stored in an environment adjusted to the aforementioned temperature and relative humidity range for 10 minutes to 3 hours, or heated at a temperature of 30°C or higher and 90°C or lower, before being bonded to a transparent component such as a front panel.

[0099] (Manufacturing method of polarization element)

[0100] There is no particular limitation on the manufacturing method of polarizing elements; however, typical methods include: a method of producing a PVA-based resin film pre-wound into a roll and then stretching, dyeing, cross-linking, etc. (hereinafter referred to as "manufacturing method 1"); and a method including a process of coating a coating liquid containing PVA-based resin onto a substrate film to form a coating layer and stretching the resulting laminate (hereinafter referred to as "manufacturing method 2").

[0101] Manufacturing method 1 may include a step of uniaxially stretching a PVA-based resin film, a step of dyeing the PVA-based resin film with a dichroic pigment such as iodine to adsorb the dichroic pigment, a step of treating the PVA-based resin film with the adsorbed dichroic pigment with a boric acid aqueous solution, and a step of washing with water after treatment with boric acid aqueous solution.

[0102] The swelling process involves immersing a PVA-based resin film in a swelling bath. Besides removing surface contaminants and adhesives from the PVA-based resin film, the swelling process also helps suppress uneven dyeing by causing the film to swell. The swelling bath typically uses a water-based medium, such as water, distilled water, or pure water. Surfactants, alcohols, etc., can be appropriately added to the swelling bath using conventional methods. From the viewpoint of controlling the potassium content of the polarizing element, potassium iodide can be used in the swelling bath. In this case, the concentration of potassium iodide in the swelling bath is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less.

[0103] The temperature of the swelling bath is preferably 10°C or higher and 60°C or lower, more preferably 15°C or higher and 45°C or lower, and even more preferably 18°C ​​or higher and 30°C or lower. Regarding the immersion time in the swelling bath, since the degree of swelling of the PVA-based resin film is affected by the temperature of the swelling bath, it cannot be fixed in general; however, it is preferably 5 seconds or higher and 300 seconds or lower, more preferably 10 seconds or higher and 200 seconds or lower, and even more preferably 20 seconds or higher and 100 seconds or lower. The swelling process can be performed only once or multiple times as needed.

[0104] The dyeing process involves immersing a PVA-based resin film in a dyeing bath, which allows dichroic pigments to be adsorbed and oriented on the PVA-based resin film. When the dichroic pigment is iodine, the dyeing bath is preferably an iodine solution. The iodine solution is typically an aqueous iodine solution containing iodine and an iodide as a dissolving agent. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is suitable from the viewpoint of controlling the potassium content in the polarizing element.

[0105] The concentration of iodine in the staining bath (iodine solution) is preferably 0.01% by mass or more and 1% by mass or less, more preferably 0.02% by mass or more and 0.5% by mass or less. The concentration of iodide in the staining bath is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.05% by mass or more and 5% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less.

[0106] The temperature of the dyeing bath is preferably 10°C or higher and 50°C or lower, more preferably 15°C or higher and 45°C or lower, and even more preferably 18°C ​​or higher and 30°C or lower. Regarding the immersion time in the dyeing bath, since the degree of dyeing of the PVA-based resin film is affected by the temperature of the dyeing bath, it cannot be fixed in general; however, it is preferably 10 seconds or higher and 300 seconds or lower, more preferably 20 seconds or higher and 240 seconds or lower. The dyeing process can be performed only once or multiple times as needed.

[0107] The crosslinking process involves immersing a PVA-based resin film, dyed during the dyeing process, in a treatment bath (crosslinking bath) containing a boron compound. The boron compound crosslinks the PVA-based resin film, allowing iodine or dye molecules to adsorb onto the crosslinked structure. Examples of boron compounds include boric acid, borates, and borax. The crosslinking bath is generally an aqueous solution; however, it can also be a mixture of an organic solvent miscible with water and water. From the viewpoint of controlling the potassium content in the polarizing element, the crosslinking bath preferably contains potassium iodide.

[0108] In the crosslinking bath, the concentration of the boron compound is preferably 1% by mass or more and 15% by mass or less, more preferably 1.5% by mass or more and 10% by mass or less, and even more preferably 2% by mass or more and 5% by mass or less. When potassium iodide is used in the crosslinking bath, the concentration of potassium iodide in the crosslinking bath is preferably 1% by mass or more and 15% by mass or less, more preferably 1.5% by mass or more and 10% by mass or less, and even more preferably 2% by mass or more and 5% by mass or less.

[0109] The temperature of the crosslinking bath is preferably 20°C or higher and 70°C or lower, more preferably 30°C or higher and 60°C or lower. Regarding the immersion time in the crosslinking bath, since the degree of crosslinking of the PVA-based resin film is affected by the temperature of the crosslinking bath, it cannot be fixed in general; however, it is preferably 5 seconds or higher and 300 seconds or lower, more preferably 10 seconds or higher and 200 seconds or lower. The crosslinking process can be performed only once or multiple times as needed.

[0110] The stretching process is a procedure in which a PVA-based resin film is stretched at least in one direction at a specified ratio. Generally, the PVA-based resin film is uniaxially stretched along the transport direction (length direction). There are no particular restrictions on the stretching method; either wet stretching or dry stretching can be used. The stretching process can be performed once or multiple times as needed. The stretching process can be performed at any stage of the manufacturing of polarization elements.

[0111] The treatment bath (stretching bath) in the wet stretching process can typically be water or a solution of water mixed with an organic solvent that is miscible with water. From the viewpoint of controlling the potassium content in the polarizing element, the stretching bath preferably contains potassium iodide. When potassium iodide is used in the stretching bath, the concentration of potassium iodide in the stretching bath is preferably 1% by mass or more and 15% by mass or less, more preferably 2% by mass or more and 10% by mass or less, and even more preferably 3% by mass or more and 6% by mass or less. From the viewpoint of suppressing film breakage during stretching, the treatment bath (stretching bath) may contain a boron compound. When a boron compound is included, the concentration of the boron compound in the stretching bath is preferably 1% by mass or more and 15% by mass or less, more preferably 1.5% by mass or more and 10% by mass or less, and even more preferably 2% by mass or more and 5% by mass or less.

[0112] The temperature of the stretching bath is preferably 25°C or higher and 80°C or lower, more preferably 40°C or higher and 75°C or lower, and even more preferably 50°C or higher and 70°C or lower. Regarding the immersion time in the stretching bath, since the degree of stretching of the PVA-based resin film is affected by the temperature of the stretching bath, it cannot be fixed in general; however, it is preferably 10 seconds or higher and 800 seconds or lower, more preferably 30 seconds or higher and 500 seconds or lower. The stretching treatment in the wet stretching method can be performed together with any one or more of the following processing steps: swelling step, dyeing step, crosslinking step, and washing step.

[0113] Examples of dry stretching methods include inter-roll stretching, heated roll stretching, and compression stretching. It should be noted that in dry stretching methods, the stretching process can be performed during the drying process.

[0114] The total stretch ratio (cumulative stretch ratio) applied to the PVA-based resin film can be appropriately set according to the purpose, preferably 2 times or more and 7 times or less, more preferably 3 times or more and 6.8 times or less, and even more preferably 3.5 times or more and 6.5 times or less.

[0115] The washing process involves immersing the PVA-based resin film in a washing bath to remove foreign matter remaining on the surface of the PVA-based resin film. The washing bath typically uses a water-based medium, such as water, distilled water, or pure water. From the viewpoint of controlling the potassium content in the polarization element, potassium iodide is preferably used in the washing bath. In this case, the concentration of potassium iodide in the washing bath is preferably 1% by mass or more and 10% by mass or less, more preferably 1.5% by mass or more and 4% by mass or less, and even more preferably 1.8% by mass or more and 3.8% by mass or less.

[0116] The temperature of the washing bath is preferably 5°C or higher and 50°C or lower, more preferably 10°C or higher and 40°C or lower, and even more preferably 15°C or higher and 30°C or lower. Regarding the immersion time in the washing bath, since the degree of washing of the PVA resin film is affected by the temperature of the washing bath, it cannot be fixed in general; however, it is preferably 1 second or higher and 100 seconds or lower, more preferably 2 seconds or higher and 50 seconds or lower, and even more preferably 3 seconds or higher and 20 seconds or lower. The washing process can be performed only once or multiple times as needed.

[0117] The drying process is the process of drying the PVA-based resin film washed in the washing process to obtain the polarizing element. Drying can be carried out using any appropriate method, such as natural drying, forced air drying, or heat drying.

[0118] Manufacturing method 2 may include a step of coating a coating liquid containing a PVA-based resin onto a substrate film, a step of uniaxially stretching the resulting laminated film, a step of adsorbing dichroic pigments by dyeing the coating layer of the uniaxially stretched laminated film with dichroic pigments, a step of treating the laminated film with adsorbed dichroic pigments with a boric acid aqueous solution, and a step of washing with water after treatment with the boric acid aqueous solution. The substrate film used to form the polarizing element can be used as a transparent protective film for the polarizing plate. The substrate film can be peeled off from the polarizing element as needed.

[0119] <Transparent Protective Film>

[0120] A transparent protective film is adhered to at least one side of the polarizing element via an adhesive layer. The transparent protective film is adhered to one or both sides of the polarizing element, but preferably to both sides.

[0121] The transparent protective film can simultaneously possess other optical functions and can also have a multi-layered structure. From an optical property point of view, a thin transparent protective film is preferred; however, if it is too thin, its strength decreases and its processability suffers. An appropriate film thickness is 5 μm or more and 100 μm or less, preferably 10 μm or more and 80 μm or less, and more preferably 15 μm or more and 70 μm or less.

[0122] The transparent protective film can be made of cellulose acylated film, film containing polycarbonate resin, film containing cyclic olefin resin such as norbornene, (meth)acrylic polymer film, polyester resin such as polyethylene terephthalate, etc. When the transparent protective film is bonded to both sides of the polarizing element using a water-based adhesive such as PVA adhesive, from the perspective of moisture permeability, it is preferable that at least one side of the transparent protective film is either a cellulose acylated film or a (meth)acrylic polymer film, with a cellulose acylated film being preferred.

[0123] At least one of the transparent protective films in the polarizing plate can have a phase difference function for purposes such as viewing angle compensation. In this case, the film constituting the transparent protective film may have a phase difference function itself, or the transparent protective film may have a layer without a phase difference function and a phase difference layer (a layer with a phase difference function). When the transparent protective film has a phase difference layer, it can be set as a laminate of a layer without a phase difference function and a phase difference layer, and these layers can be bonded together using an adhesive or bonding agent.

[0124] <Adhesive layer>

[0125] An adhesive containing the first and second compounds is used as the adhesive layer for bonding the transparent protective film to the polarizing element. The adhesive can be a water-based adhesive, a solvent-based adhesive, or an active energy radiation-cured adhesive, but a water-based adhesive is preferred, and preferably contains a PVA-based resin. By using an adhesive containing the first and second compounds to form the adhesive layer, the decrease in transmittance of the polarizing plate under high-temperature conditions can be suppressed.

[0126] The thickness of the adhesive coating can be set to any value. For example, it can be set in such a way that an adhesive layer with a desired thickness is obtained after curing or heating (drying). The thickness of the adhesive layer is preferably 0.01 μm or more and 7 μm or less, more preferably 0.01 μm or more and 5 μm or less, further preferably 0.01 μm or more and 2 μm or less, and most preferably 0.01 μm or more and 1 μm or less.

[0127] When manufacturing a polarizing plate using a polarizing element that does not contain the first compound and the second compound, the content of the first compound and the second compound in the adhesive is preferably within the range described below. When manufacturing a polarizing plate using a polarizing element containing the first compound and the second compound, the content of the first compound and the second compound in the adhesive can be appropriately changed from the range described below, corresponding to the first compound and the second compound contained in the polarizing element. Specific examples of the first compound and the second compound are as described above.

[0128] When the adhesive contains PVA-based resin (e.g., an aqueous adhesive containing PVA-based resin), the content of the first compound relative to 100 parts by weight of the PVA-based resin is preferably 0.1 parts by weight or more and 400 parts by weight or less, more preferably 1 part by weight or more and 200 parts by weight or less, and even more preferably 3 parts by weight or more and 100 parts by weight or less. If it is less than 0.1 parts by weight, the inhibition effect on polyene formation of the PVA-based resin under high-temperature conditions may be insufficient. On the other hand, if it is greater than 400 parts by weight, the first compound may precipitate after the polarizing plate is manufactured.

[0129] When the adhesive contains PVA-based resin (e.g., an aqueous adhesive containing PVA-based resin), the content of the second compound relative to 100 parts by weight of the PVA-based resin is preferably 1 part by weight or more and 50 parts by weight or less, more preferably 1.5 parts by weight or more and 40 parts by weight or less, and even more preferably 2 parts by weight or more and 35 parts by weight or less. If it is less than 1 part by weight, the inhibition effect on polyene formation of the PVA-based resin under high-temperature conditions may be insufficient. On the other hand, if it is more than 50 parts by weight, the second compound may precipitate after the polarizing plate is manufactured.

[0130] In a configuration in which a transparent protective film is bonded to both sides of a polarizing element via an adhesive layer, the adhesive layer on both sides of the polarizing element may have only one adhesive layer containing both the first compound and the second compound, but it is preferable that both adhesive layers contain both the first compound and the second compound.

[0131] To meet the demand for thinner polarizing plates, a polarizing plate with a transparent protective film on only one side of the polarizing element has been developed. In this configuration, the transparent protective film is also laminated via an adhesive layer containing a first compound and a second compound. As a method for manufacturing this type of polarizing plate with a transparent protective film on only one side of the polarizing element, a method can be considered whereby a polarizing plate with transparent protective films adhered to both sides via adhesive layers is first manufactured, and then one transparent protective film is peeled off. In using this manufacturing method, only one adhesive layer may contain both the first and second compounds; however, it is preferable that both adhesive layers contain both the first and second compounds. When only one adhesive layer contains both the first and second compounds, it is preferable that the adhesive layer on the non-peeled film side contains both the first and second compounds.

[0132] (Water-based adhesive)

[0133] Any suitable aqueous adhesive can be used as the aqueous adhesive; however, it is preferred to use an aqueous adhesive containing PVA-based resin (PVA-based adhesive). Regarding the average degree of polymerization of the PVA-based resin contained in the aqueous adhesive, from an adhesiveness perspective, it is preferably 100 or more and 5500 or less, more preferably 1000 or more and 4500 or less. Regarding the average degree of saponification, from an adhesiveness perspective, it is preferably 85 mol% or more and 100 mol% or less, more preferably 90 mol% or more and 100 mol% or less.

[0134] As the PVA-based resin contained in the water-based adhesive, a PVA-based resin containing acetyl groups is preferred (hereinafter sometimes referred to as "acetyl-containing PVA-based resin"). This is because the PVA-based resin layer exhibits excellent adhesion to the transparent protective film and excellent durability. The acetyl-containing PVA-based resin can be obtained, for example, by reacting a PVA-based resin with a diene using any method. The degree of acetyl-containing modification of the PVA-based resin is typically 0.1 mol% or more, preferably 0.1 mol% or more and 20 mol% or less. The resin concentration of the water-based adhesive is preferably 0.1% by mass or more and 15% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less.

[0135] Water-based adhesives can also contain crosslinking agents. Known crosslinking agents can be used. Examples of crosslinking agents include water-soluble epoxy compounds, dialdehydes, and isocyanates.

[0136] When the PVA resin is a PVA resin containing acetyl groups, the crosslinking agent is preferably any one of glyoxal, glyoxylate, or hydroxymethyl melamine, more preferably any one of glyoxal or glyoxylate, and particularly preferably glyoxal.

[0137] Aqueous adhesives may also contain organic solvents. From the perspective of miscibility with water, alcohols are preferred organic solvents, and methanol or ethanol are more preferred among alcohols. The concentration of methanol in the aqueous adhesive is preferably 10% by mass or more and 70% by mass or less, more preferably 15% by mass or more and 60% by mass or less, and even more preferably 20% by mass or more and 60% by mass or less. By keeping the methanol concentration at 10% by mass or more, it is easier to further suppress the polyene formation of PVA-based resins under high-temperature conditions. Furthermore, by keeping the methanol content at 70% by mass or less, color deterioration can be suppressed. For example, as a component incorporated into an aqueous adhesive, sometimes a component with low solubility in water but sufficient solubility in alcohol is used. In this case, it is also a preferred method to prepare the adhesive by dissolving the component in an alcohol to prepare an alcohol solution of the component and then adding the alcohol solution to an aqueous solution of PVA-based resin.

[0138] (Active energy radiation curing adhesive)

[0139] Reactive energy radiation-cured adhesives are adhesives that are cured by irradiation with reactive energy rays such as ultraviolet light. Examples include adhesives containing polymerizable compounds and photopolymerization initiators, adhesives containing photoreactive resins, and adhesive resins containing photoreactive crosslinking agents. Examples of polymerizable compounds include photopolymerizable monomers such as photocurable epoxy monomers, photocurable acrylic monomers, and photocurable urethane monomers, as well as oligomers derived from these monomers. Examples of photopolymerization initiators include compounds containing substances that generate reactive species such as neutral free radicals, anionic free radicals, and cationic free radicals upon irradiation with reactive energy rays such as ultraviolet light.

[0140] [Manufacturing method of polarizing plate]

[0141] The polarizing plate manufacturing method of this embodiment includes a lamination process of stacking polarizing elements and a transparent protective film. The polarizing plate manufacturing method may also include a moisture content adjustment process. The order in which the moisture content adjustment process and the lamination process are performed is not limited, and the moisture content adjustment process and the lamination process may be performed in parallel.

[0142] In the lamination process, the polarizing element and the transparent protective film are laminated using the aforementioned adhesive layer. In the lamination process, the polarizing element and the transparent protective film are bonded together using an adhesive containing a first compound and a second compound. The adhesive sandwiched between the polarizing element and the transparent protective film becomes an adhesive layer, for example, through a drying process. The lamination process can also be a process of bonding a polarizing element without the first and second compounds to the transparent protective film using an adhesive containing both compounds. In this case, during the formation of the adhesive layer from the adhesive, a portion of the first and second compounds contained in the adhesive can move to the polarizing element, etc.

[0143] In the moisture content adjustment process, when manufacturing a polarizing plate with characteristic (a), the moisture content of the polarizing element is adjusted such that it is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C. The moisture content of the polarizing element can be adjusted using the method described above. In the moisture content adjustment process, when manufacturing a polarizing plate with characteristic (b), the moisture content of the polarizing plate is adjusted such that it is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C. The moisture content of the polarizing plate can be adjusted using the method described above.

[0144] [Composition of an image display device]

[0145] The polarizing plate of this embodiment is used in various image display devices such as liquid crystal display devices and organic EL display devices. In image display devices with an interlayer filling configuration where a solid layer other than an air layer, specifically an adhesive layer, is in contact with both sides of the polarizing plate, the transmittance tends to decrease at high temperatures. In image display devices using the polarizing plate of this embodiment, even with an interlayer filling configuration, the decrease in the transmittance of the polarizing plate at high temperatures can be suppressed.

[0146] Examples of solid layers include adhesive layers or bonding agent layers. When the solid layer is an adhesive layer, it is preferable to use an adhesive layer formed with a UV-curable adhesive.

[0147] As an image display device, an example can be illustrated by a configuration having an image display unit, a first adhesive layer laminated to the viewing-side surface of the image display unit, and a polarizing plate laminated to the viewing-side surface of the first adhesive layer. This image display device may further include a second adhesive layer laminated to the viewing-side surface of the polarizing plate and a transparent component laminated to the surface of the second adhesive layer. In particular, the polarizing plate of this embodiment can be suitably used in an image display device having an interlayer filling configuration, wherein a transparent component is disposed on the viewing side of the image display device, the polarizing plate is bonded to the image display unit using the first adhesive layer, and the polarizing plate is bonded to the transparent component using the second adhesive layer.

[0148] The polarizing plate and the image display unit are not limited to being bonded using the first adhesive layer, but can also be bonded using an adhesive layer formed using an adhesive. Similarly, the polarizing plate and the transparent component are not limited to being bonded using the second adhesive layer, but can also be bonded using an adhesive layer formed using an adhesive. The adhesive can be the adhesive described above, or an adhesive that does not contain the first compound and the second compound.

[0149] <Image Display Unit>

[0150] Examples of image display units include liquid crystal units (LCDs) and organic EL units (OLEDs). As a liquid crystal unit, one can use a reflective liquid crystal unit that utilizes external light, a transmissive liquid crystal unit that utilizes light from a light source such as a backlight, or a semi-transmissive / semi-reflective liquid crystal unit that utilizes both external light and light from a light source. When the liquid crystal unit utilizes light from a light source, the image display device (liquid crystal display device) also provides a polarizing plate on the side of the image display unit (liquid crystal unit) opposite to the viewing side, and further provides a light source. The polarizing plate on the light source side is preferably bonded to the liquid crystal unit via a suitable adhesive layer. As for the driving method of the liquid crystal unit, any type of driving method can be used, such as VA mode, IPS mode, TN mode, STN mode, or π-type bending orientation.

[0151] As an organic EL unit, an organic EL unit in which a transparent electrode, an organic light-emitting layer, and a metal electrode are sequentially stacked on a transparent substrate to form a light emitter (organic electroluminescent body) can be appropriately used. The organic light-emitting layer is a stack of various organic thin films, such as a stack of a hole injection layer containing a triphenylamine derivative and a light-emitting layer containing a fluorescent organic solid such as anthracene, a stack of these light-emitting layers and an electron injection layer containing a perylene derivative, or a stack of a hole injection layer, a light-emitting layer, and an electron injection layer, etc.

[0152] <Attachment of image display unit to polarizing plate>

[0153] In the bonding of the image display unit and the polarizing plate, a first adhesive layer can be appropriately used. From an operability perspective, it is preferable to bond the image display unit to a polarizing plate with the first adhesive layer attached to one side of the polarizing plate. The attachment of the first adhesive layer to the polarizing plate can be performed in a suitable manner. Examples include preparing an adhesive solution containing approximately 10% by mass and 40% by mass or a combination thereof of a base polymer dissolved or dispersed in a solvent containing a suitable solvent such as toluene or ethyl acetate, and directly attaching it to the polarizing plate using a suitable spreading method such as casting or coating; or transferring the first adhesive layer to the polarizing plate after forming it on a release film.

[0154] <First adhesive layer, second adhesive layer>

[0155] The first adhesive layer and the second adhesive layer (hereinafter, either or both may be referred to as "adhesive layer") may be formed independently of one or more layers, but preferably of one layer. The adhesive layer may be composed of an adhesive composition with (meth)acrylic resin, rubber resin, urethane resin, ester resin, silicone resin, or polyvinyl ether resin as the main component. Among these, an adhesive composition with a (meth)acrylic resin as the base polymer, possessing excellent transparency, weather resistance, and heat resistance, is suitable. The adhesive composition may also be of the active energy radiation curing type or the thermosetting type.

[0156] The (meth)acrylic resin (base polymer) used in the adhesive composition can suitably be a polymer or copolymer with one or more (meth)acrylate monomers such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. It is preferable to copolymerize the polar monomer with the base polymer. Examples of polar monomers include (meth)acrylic acid compounds, 2-hydroxypropyl (meth)acrylate compounds, hydroxyethyl (meth)acrylate compounds, (meth)acrylamide compounds, N,N-dimethylaminoethyl (meth)acrylate compounds, and glycidyl (meth)acrylate compounds, which have carboxyl, hydroxyl, amide, amino, or epoxy groups.

[0157] The adhesive composition may contain only the aforementioned base polymer, but typically also contains a crosslinking agent. Examples of crosslinking agents include metal ions that are divalent or higher metal ions and form a carboxylic acid metal salt therebetween with a carboxyl group; polyamine compounds that form an amide bond with a carboxyl group; polyepoxide compounds or polyols that form an ester bond with a carboxyl group; and polyisocyanate compounds that form an amide bond with a carboxyl group. Among these, polyisocyanate compounds are preferred.

[0158] The active energy radiation-curable adhesive composition possesses the property of curing upon irradiation with active energy radiation such as ultraviolet rays or electron beams. It also exhibits adhesiveness even before irradiation, enabling it to adhere tightly to substrates such as films, and the ability to adjust the adhesion force through curing upon irradiation. The active energy radiation-curable adhesive composition is preferably ultraviolet-curable. In addition to containing a base polymer and a crosslinking agent, the active energy radiation-curable adhesive composition also contains an active energy radiation-polymerizable compound. Depending on the requirements, it may contain photopolymerization initiators, photosensitizers, etc.

[0159] The adhesive composition may contain additives such as microparticles, beads (resin beads, glass beads, etc.) for imparting light scattering properties, glass fibers, resins other than the base polymer, tackifiers, fillers (metal powders, other inorganic powders, etc.), antioxidants, ultraviolet absorbers, dyes, pigments, colorants, defoamers, corrosion inhibitors, and photopolymerization initiators.

[0160] The adhesive layer can be formed by applying an organic solvent dilution of the adhesive composition described above to the surface of a substrate film, an image display unit, or a polarizing plate and then drying it. The substrate film is typically a thermoplastic resin film; a typical example is a release film that has undergone a release treatment. The release film can be, for example, a film in which the adhesive layer of a film containing resins such as polyethylene terephthalate, polybutylene terephthalate, polycarbonate, or polyarylate has undergone a release treatment such as silicone treatment.

[0161] An adhesive composition can be directly applied to the release surface of the release film to form an adhesive layer, and this adhesive layer with the release film can be laminated onto the surface of the polarizing plate. Alternatively, an adhesive composition can be directly applied to the surface of the polarizing plate to form an adhesive layer, and a release film can be laminated on the outer surface of the adhesive layer.

[0162] When the adhesive layer is applied to the surface of the polarizing plate, it is preferable to perform surface activation treatments such as plasma treatment or corona treatment on the bonding surface of the polarizing plate and / or the bonding surface of the adhesive layer, and more preferably to perform corona treatment.

[0163] Alternatively, an adhesive sheet can be prepared by coating an adhesive composition onto a second release liner to form an adhesive layer, and then laminating a release liner onto the formed adhesive layer. The adhesive layer with the release liner after peeling off the second release liner from the adhesive sheet is then laminated onto a polarizing plate. The second release liner is a membrane with weaker adhesion to the adhesive layer and easier to peel off compared to the release liner.

[0164] The thickness of the adhesive layer is not particularly limited, but is preferably 1 μm or more and 100 μm or less, more preferably 3 μm or more and 50 μm or less, and may also be 20 μm or more.

[0165] <Transparent Components>

[0166] Examples of transparent components that can be used as the viewing side of an image display device include transparent panels (front panels, window layers) and touch panels. The transparent panel should have appropriate mechanical strength and thickness. Examples of such transparent panels include transparent resin sheets made of polyimide, acrylic, or polycarbonate resins, or glass. Functional layers such as anti-reflective layers can also be laminated on the viewing side of the transparent panel. Furthermore, when the transparent panel is a transparent resin sheet, a hard coating can be laminated to improve physical strength, and a low-permeability layer can be laminated to reduce moisture permeability. As for the touch panel, various types of touch panels can be used, such as resistive film, capacitive, optical, and ultrasonic touch panels, as well as glass panels and transparent resin sheets with touch sensor functionality. When using a capacitive touch panel as the transparent component, it is preferable to provide a transparent panel made of glass or a transparent resin sheet on the viewing side relative to the touch panel.

[0167] <Fitting of polarizing plate with transparent component>

[0168] In bonding the polarizing plate to the transparent component, adhesives or active energy radiation-cured adhesives can be appropriately used. When using adhesives, they can be applied in a suitable manner. As a specific application method, the adhesive layer application method used in the bonding of the image display unit and the polarizing plate described above can be cited as an example.

[0169] When using an active energy ray-cured adhesive, to prevent the adhesive solution from spreading before curing, a suitable method can be used as follows: a dam material is set up to surround the periphery of the image display panel; a transparent component is placed on the dam material; and the adhesive solution is injected. After the adhesive solution is injected, alignment and degassing are performed as needed, followed by curing by irradiation with active energy rays.

[0170] Example

[0171] The present invention will now be specifically described based on embodiments. The materials, reagents, quantities, proportions, and operations shown in the following embodiments can be appropriately modified without departing from the spirit of the invention. Therefore, the present invention is not limited or restricted by the following embodiments.

[0172] <Fabrication of Polarizing Element A>

[0173] A 40 μm thick PVA-based resin film containing PVA-based resin with an average degree of polymerization of approximately 2400 and a saponification degree of 99.9 mol% or higher was uniaxially stretched to approximately 5 times its original length using a dry method. While maintaining this tension, the film was immersed in pure water at 60°C for 1 minute, followed by immersion in an aqueous solution of iodine / potassium iodide / water at 28°C for 60 seconds. Subsequently, it was immersed in an aqueous solution of potassium iodide / boric acid / water at 72°C for 300 seconds. After washing with pure water at 26°C for 20 seconds, the film was dried at 65°C to obtain a 15 μm thick polarizing element A with iodine adsorbed and oriented in the PVA-based resin layer. The thickness of polarizing element A was measured using a digital micrometer "MH-15M" manufactured by Nikon Corporation.

[0174] <Preparation of Adhesives 1-5>

[0175] (Preparation of PVA solution A for adhesives)

[0176] 50g of a modified PVA resin containing acetyl groups ("Gohsenx Z-410" manufactured by Mitsubishi Chemical Corporation) was dissolved in 950g of pure water. The solution was heated at 90°C for 2 hours and then cooled to room temperature to obtain PVA solution A for adhesives.

[0177] (Preparation of adhesives 1-5)

[0178] Adhesives 1 to 5 were prepared by mixing PVA solution A, compound 1, compound 2, and pure water, with the concentration of PVA-based resin being 3.0% by mass and the contents of compound 1 and compound 2 as shown in Table 1. 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxygen radical (hereinafter also referred to as "TEMPOL") was used as compound 1.

[0179] [Table 1]

[0180]

[0181] ※: Content in 100 parts by weight of PVA-based resin

[0182] <Preparation of Transparent Protective Film A>

[0183] A commercially available cellulose acylated membrane (Fujifilm Corporation "TD40", 40 μm thick) was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) at 55°C for 2 minutes, followed by washing with water. Then, it was immersed in a 0.05 mol / L sulfuric acid aqueous solution at 25°C for 30 seconds, and subsequently passed through a water bath under running water for 30 seconds to neutralize the cellulose acylated membrane. After repeated dehydration three times using an air knife, it was dried in a drying zone at 70°C for 15 seconds to produce a saponified cellulose acylated membrane, serving as transparent protective film A.

[0184] <Preparation of Polarizing Plate 1>

[0185] Using a roller laminator, adhesive 1 is applied to both sides of the polarizing element A, followed by bonding of a transparent protective film A. The film is then dried at 80°C for 5 minutes to form an adhesive layer, resulting in the polarizing plate 1. The amount of adhesive 1 used is adjusted so that the thickness of the dried adhesive layer is 50 nm on both sides.

[0186] <Preparation of Polarizing Plates 2-5>

[0187] Except for changing adhesive 1 to adhesive 2 to 5, polarizing plates 2 to 5 are obtained in the same manner as the polarizing plate 1 described above.

[0188] (Adjustment of moisture content in polarizing plate (polarizing element))

[0189] The polarizing plates 1-5 obtained above were stored at 20°C and 40% relative humidity for 72 hours. The moisture content was determined using the Karl Fischer method after 66, 69, and 72 hours from the start of storage. Since no change was observed in the measured moisture content values, the moisture content of polarizing plates 1-5 can be considered the same as the equilibrium moisture content under the 72-hour storage environment. When the moisture content of a polarizing plate reaches equilibrium under a certain storage environment, the moisture content of the polarizing element within the polarizing plate can also be considered to have reached equilibrium under that storage environment. Furthermore, when the moisture content of the polarizing element within a polarizing plate reaches equilibrium under a certain storage environment, the moisture content of the polarizing plate can also be considered to have reached equilibrium under that storage environment.

[0190] <High Temperature Durability Evaluation>

[0191] (Preparation of the evaluation sample)

[0192] An adhesive layer was formed on both sides of polarizers 1-5 after adjusting the moisture content using an acrylic adhesive (manufactured by LINTEC Corporation, model: #7). Polarizers 1-5 were cut to a size of 50mm × 100mm with the absorption axis parallel to the long side, and alkali-free glass (manufactured by Corning Corporation, "EAGLE XG") was laminated onto the surface of each adhesive layer to produce evaluation samples.

[0193] (Evaluation based on the change in transmittance during high-temperature durability testing (105℃))

[0194] The evaluation samples were subjected to a temperature of 50℃ and a pressure of 5 kgf / cm². 2 After undergoing autoclave treatment for 1 hour at (490.3 kPa), the sample was placed in an environment with a temperature of 23°C and a relative humidity of 55% for 24 hours. A spectroradiometer (SR-UL1R, manufactured by Topcon Technohouse Co., Ltd.) was used to measure the light intensity at 5000 cd / m². 2 The evaluation sample was placed on the illumination surface of the backlight module, and its brightness was measured at a measurement angle of 2 degrees and a measurement distance of 350 mm. The brightness measured under these conditions was designated as "Brightness L0". Subsequently, the evaluation sample was stored in a heating environment at 105°C for 72 to 240 hours, and its brightness was measured every 24 hours using the same procedure as above. The measured brightness was designated as "Brightness L1" as the brightness after the high-temperature durability test.

[0195] Using the measured luminance L0 and luminance L1, calculate the change in transmittance according to the following formula.

[0196] Change in transmittance [%) = 100 - (brightness L1 / brightness L0) × 100

[0197] Based on the storage time under the aforementioned heating environment required to obtain luminance L1 with a transmittance change of 5% or more, high-temperature durability was evaluated according to the following evaluation criteria. The results are shown in Table 2.

[0198] (Evaluation Criteria)

[0199] The required storage time of the evaluation sample under heating environment until the change in transmittance of the evaluation sample reaches 5% or more.

[0200] Evaluation samples with an duration of more than 240 hours: A

[0201] Evaluation samples for periods longer than 120 hours but up to 240 hours: B

[0202] Evaluation samples longer than 72 hours but up to 120 hours: C

[0203] Evaluation samples up to 72 hours: D

[0204] [Table 2]

[0205]

[0206] ※: Content in 100 parts by weight of PVA-based resin.

Claims

1. A polarizing plate comprising a polarizing element obtained by adsorbing and oriented a dichroic pigment onto a polyvinyl alcohol-based resin layer, and a transparent protective film laminated on at least one side of the polarizing element. The polarizing element and the transparent protective film are bonded together using an adhesive layer formed from an adhesive containing the first compound and the second compound. The adhesive is a water-based adhesive. The first compound is a compound containing nitryl radicals or nitroxy radicals. The second compound is selected from at least one of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin.

2. The polarizing plate according to claim 1, wherein, The first compound is an N-oxygen free radical compound.

3. The polarizing plate according to claim 1 or 2, wherein, The second compound is α-cyclodextrin.

4. The polarizing plate according to any one of claims 1 to 3, wherein, The adhesive comprises a polyvinyl alcohol-based resin.

5. The polarizing plate according to claim 4, wherein, In the adhesive, the content of the first compound is 0.1 parts by weight or more and 400 parts by weight or less relative to 100 parts by weight of the polyvinyl alcohol resin.

6. The polarizing plate according to claim 4 or 5, wherein, In the adhesive, the content of the second compound is more than 1 part by weight and less than 50 parts by weight relative to 100 parts by weight of the polyvinyl alcohol resin.

7. The polarizing plate according to any one of claims 1 to 6, wherein, The thickness of the adhesive layer is greater than 0.01 μm and less than 7 μm.

8. The polarizing plate according to any one of claims 1 to 7, wherein, The polarizing plate is used in an image display device. In the image display device, a solid layer is provided in contact with both sides of the polarizing plate.

9. An image display device comprising an image display unit, a first adhesive layer laminated on the observation-side surface of the image display unit, and a polarizing plate laminated on the observation-side surface of the first adhesive layer, as described in any one of claims 1 to 8.

10. The image display device according to claim 9, further comprising a second adhesive layer laminated on the observation-side surface of the polarizing plate, and a transparent component laminated on the observation-side surface of the second adhesive layer.

11. The image display device according to claim 10, wherein, The transparent component is a glass plate or a transparent resin plate.

12. The image display device according to claim 10, wherein, The transparent component is a touch panel.

Citation Information

Patent Citations

  • Liquid crystal panel support, electronic equipment having the same and manufacture of the same equipment

    JP1999174417A

  • Production of high-purity (Meth)Acrylic acid ester

    JP1999222462A

  • Method for diminishing n-oxyl compound

    JP2002284737A

  • Method of producing polyfunctional vinyl compound

    JP2003064022A

  • Polarizing plate and image display device, and manufacturing method of those

    JP2014102353A